Television and the meaning of live an enquiry into the human situation - Scannell, Paddy (Polity, 2014)
This book is about the question of existence, the meaning of life. It is an enquiry into the contemporary human situation as disclosed by television. Passionate and sweeping in scale, this book from a leading media scholar is a major contribution to our understanding of the media today